The Effect of Job Description Clarity and Work System Effectiveness on Employee Productivity - Safri Tahir; Mattalatta Mattalatta; Ansar Ansar; Kurniawaty Kurniawaty (Pustaka Digital Indonesia, 2026)
This study aims to analyze the influence of job descriptions and work systems on employee productivity at PT. PLN (Persero) South Sulawesi Region. The study employs a quantitative approach using the explanatory research method. Primary data were collected through the distribution of questionnaires to 80 respondents using a census technique. Data analysis included validity and reliability tests, multiple linear regression, t-tests, and the coefficient of determination (R²). The results indicate that job descriptions and work systems have a positive and significant effect on work productivity. The regression equation obtained is: Y = 2.865 + 0.311X? + 0.518X?. The significance value of both variables, 0.000 < 0.05, indicates a significant influence. The work system is the most dominant variable influencing work productivity. The model explains 76% of the variation in work productivity, while 24% is influenced by other factors